2002
DOI: 10.1002/gene.10161
|View full text |Cite
|
Sign up to set email alerts
|

vavCre Transgenic mice: A tool for mutagenesis in hematopoietic and endothelial lineages

Abstract: Cre transgenic mice can be used to delete gene sequences flanked by loxP sites in specific somatic tissues. We have generated vavCre transgenic mice, which can be used to inactivate genes specifically in adult hematopoietic and endothelial cells. In these animals, a Cre transgene is expressed under control of murine vav gene regulatory elements. To assess their usefulness, vavCre transgenic mice were bred with R26R mice, which express a lacZ reporter gene only in cells where Cre-mediated recombination has occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
177
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 195 publications
(190 citation statements)
references
References 19 publications
11
177
2
Order By: Relevance
“…The control animals used for this study were heterozygous for the deleted and floxed Tfr2 alleles.This was done to avoid potential issues due to germ-line transmission of the Vav-Cre 1/2 allele, as previously reported [25]. Previous studies have shown that haplo-insufficiency of TFR2 does not alter systemic iron metabolism and a single allele in the heterozygous animals is sufficient to maintain appropriate iron levels [11,12].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The control animals used for this study were heterozygous for the deleted and floxed Tfr2 alleles.This was done to avoid potential issues due to germ-line transmission of the Vav-Cre 1/2 allele, as previously reported [25]. Previous studies have shown that haplo-insufficiency of TFR2 does not alter systemic iron metabolism and a single allele in the heterozygous animals is sufficient to maintain appropriate iron levels [11,12].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that haplo-insufficiency of TFR2 does not alter systemic iron metabolism and a single allele in the heterozygous animals is sufficient to maintain appropriate iron levels [11,12]. It has been suggested that the Vav-Cre allele could be expressed in the ovaries, hence increasing the chance of germ-line transmission through the females [25,26]. In view of this, only mice generated from a breeding between a Cre 1/2 male were used for the analyses performed in this study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations